Perforated diverticulitis leading to Fournier’s gangrene - Watter, Henry K.; Choi, Ho Nam; Munugani, Suresh (International Surgery Journal, 2022)
Perforated diverticulitis is a rare cause of Fournier’s gangrene. Management for these conditions separately is well established, however no clear guidelines exist for operative management when they present in combination. This case provides a suggested management approach for managing the two conditions concurrently, in a peripheral hospital.